Kepedulian Mahasiswa Melalui Pembagian Sembako dan Obat-Obatan Dasar Kepada Masyarakat Kurang Mampu di Kelurahan Kepuh Kiriman Sidoarjo - Nelud Darajaatul Aliyah; Wulandaroini Sucianingsih; Rahayu Mardika Ningsih; Didit Darmawan; Abdul Khobir Rahmatullah (JURPIKAT, 2026)
This service was carried out in response to the socio-economic conditions of underprivileged communities in Kelurahan Kepuh Kiriman, Sidoarjo, who face challenges in meeting their food and basic healthcare needs. Through collaboration between students, local village officials, and community members, the distribution of basic food packages and essential medicines was conducted, designed in accordance with the real needs of the residents. This activity employed a participatory qualitative approach using the Participatory Action Research (PAR) method, where the community was actively involved from the preparation, implementation, to the reflection stages. The evaluation stage was conducted through open discussions and SWOT analysis to identify the program's strengths, weaknesses, opportunities, and challenges. The results of the activity showed that this assistance provided a dual impact: materially helping to stabilize family economies in the short term, and socially strengthening support networks and the sense of togetherness in the community. The community response has been overwhelmingly positive, with many recipients stating that this assistance eased their burdens and provided a sense of care. Furthermore, this activity has raised awareness of health and food security at the household level. Thus, this community service activity is not only assistance but also empowering, encouraging independence, and strengthening social solidarity in achieving shared prosperity.